2005
DOI: 10.1081/css-200059044
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Speciation of Cadmium, Copper, and Lead in Soil Solutions

Abstract: Determination of chemical speciation of trace metals may help us to better understand the bioavailability and toxicity to living organisms in terrestrial and aquatic environments. This paper reports the speciation data of cadmium (Cd), copper (Cu), and lead (Pb) in soil solutions sampled from areas around metal smelters. A column ion exchange technique (IET) using a cation exchange resin was applied to determine the concentrations of Cd 2þ , Cu 2þ , and Pb 2þ . It was shown that the pH and the amount of calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Ge et al (2005) have also found that the results of the IET were comparable with ion selective electrode (ISE) measurements for copper and satisfactory (within one order of magnitude) with anodic stripping voltammetry (ASV) measurements for Cd and Pb in lysimeter soil solutions from forest floors contaminated by trace metals. ASV measures the labile fraction, which is a representative sum of free metal ion and its inorganic and weakly dissociated metal-organic complexes.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Ge et al (2005) have also found that the results of the IET were comparable with ion selective electrode (ISE) measurements for copper and satisfactory (within one order of magnitude) with anodic stripping voltammetry (ASV) measurements for Cd and Pb in lysimeter soil solutions from forest floors contaminated by trace metals. ASV measures the labile fraction, which is a representative sum of free metal ion and its inorganic and weakly dissociated metal-organic complexes.…”
mentioning
confidence: 66%
“…In order to ensure that equilibrium was established, the last 15 ml of the effluent of each test sample was collected and tested. It is interesting to note that literature on IET, using similar conditions (especially resin mass) but testing metals other than nickel, report that only *20 ml of sample volume was required to reach steady-state (Fortin and Campbell 1998;Ge et al 2005). Nickel may be special as it was known to have slow equilibrium kinetics in natural waters (Xue et al 2001).…”
Section: Calibration Of the Column Ietmentioning
confidence: 96%
See 1 more Smart Citation
“…Regardless of these current limitations, computer models are often used in combination with data obtained by instrumental speciation techniques when assessing trace element speciation in the soil solution or in soil extracts (for example [147]), or to cross-validate the instrumental speciation techniques (for example [149]) or the models themselves (for example [150]) in various development stages.…”
Section: Models For Predicting Metal Speciation In Soil Solutionmentioning
confidence: 99%
“…, and Zn 2? concentrations in synthetic and soil solutions containing various inorganic and organic ligands, including humic substances (Doig and Liber 2007;Fortin and Campbell 1998;Ge et al 2005;Holm et al 1995;Néron et al 2006;Vigneault and Campbell 2005). The IET was successfully used for Zn 2?…”
Section: Introductionmentioning
confidence: 99%